Evaluation of Allelopathic Activity of Chinese Medicinal Plants and Identification of Shikimic Acid as an Allelochemical from Illicium verum Hook. f. - Aniya; Yoshihiro Nomura; Fuerdeng; Kwame Sarpong Appiah; Yoshiharu Fujii (Plants, 2020)
This study focused on the potential allelopathy of 50 species of Chinese medicinal plants, which are mainly distributed in the Xinjiang Uyghur Autonomous Region, Inner Mongolia, and Yunnan Province. The “sandwich method” was adopted and used for the screening for allelopathic potential among these plant species. Further phytotoxic evaluation of the candidate species was conducted by applying plant extracts to crops and weed species. The results of this study indicated that among the 50 medicinal plant species evaluated, the fruits of Illicium verum Hook. f. (star anise) showed the most significant allelopathic potential through the leaf leachates. Shikimic acid was identified to be the main bioactive compound (about 7% dry weight) in star anise by reversed-phase High Performance Liquid Chromatography (RP-HPLC) analysis. The phytotoxic bioassay indicated that both the crude extract of the Chinese star anise and the synthetic shikimic acid showed strong inhibitory activity on the radicle and hypocotyl growth of lettuce. The radicle growth inhibition of lettuce caused by the crude extract of star anise could be explained by the contribution of the biological activity of shikimic acid. In conclusion, shikimic acid could be a putative allelochemical in the fruits of Illicium verum and could be utilized in sustainable weed management.